2001
DOI: 10.1103/physrevlett.87.066403
|View full text |Cite
|
Sign up to set email alerts
|

Class of Exactly Solvable Pairing Models

Abstract: We present three classes of exactly solvable models for fermion and boson systems, based on the pairing interaction. These models are solvable in any dimension. As an example we show the first results for fermion interacting with repulsive pairing forces in a two dimensional square lattice. Inspite of the repulsive pairing force the exact results show attractive pair correlations. PACS number: 71.10. Li, 74.20.Fg Exactly solvable models have played an important role in understanding the physics of the quant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
293
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(300 citation statements)
references
References 17 publications
7
293
0
Order By: Relevance
“…Following Gaudin [6] and Dukelsky et al [12], it is possible to obtain a set of conditions for which the set of operators R i commute mutually. These are given by…”
Section: A Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Gaudin [6] and Dukelsky et al [12], it is possible to obtain a set of conditions for which the set of operators R i commute mutually. These are given by…”
Section: A Definitionsmentioning
confidence: 99%
“…For most of these systems, computationally inexpensive expressions are also known for several form factors and overlaps, which can be used to investigate observables in systems where the Hilbert space is too large for traditional exact methods. Unfortunately, the Bethe ansatz or Richardson-Gaudin equations [6,11,12] that need to be solved are highly nonlinear and give rise to singularities, making a straightforward numerical solution challenging [13,14]. Several methods have been introduced as a way to resolve this difficulty, such as a change in variables [14,15], a (pseudo)deformation of the algebra [16,17], or a Heine-Stieltjes connection, reducing the problem to a differential equation [18].…”
Section: Introductionmentioning
confidence: 99%
“…To access larger systems and fully recover the bulk limit, fixed-n projected variational BCS wavefunctions (PBCS) were used in [9] (for n ≤ 600); significant improvements over the latter results, in particular in the crossover regime, were subsequently achieved in [10] using the density matrix renormalization group (DMRG) (with n ≤ 400). Finally, Dukelsky and Schuck [11] showed that a self-consistent RPA approach, that in principle can be extended to finite temperatures, describes the f.d. regime rather well (though not as well as the DMRG).…”
Section: Comparison With Other Approachesmentioning
confidence: 99%
“…BCS approach [2,3,4] was applied to a reduced BCS Hamiltonian for uniformly spaced, spin-degenerate levels; it suggested that pairing correlations, as measured by the condensation energy E C , vanish abruptly once d exceeds a critical level spacing d c that depends on the parity (0 or 1) of the number of electrons on the grain, being smaller for odd grains (d c 1 ≃ 0.89∆) than even grains (d c 0 ≃ 3.6∆). A series of more sophisticated canonical approaches (summarized in Section 3 below) confirmed the parity dependence of pairing correlations, but established [6]- [11] that the abrupt vanishing of pairing correlations at d c is an artifact of g.c.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation